Wind Instruments: Brass - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see and hear remarkable performances on some modern brass instruments - - Learn how brass instruments produce their sound - - Hear a remarkable young tuba soloist as well as a whole ensemble of tubas - - Hear renowned artists perform in a brass quintet.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - Student Follow-up - - Correlations with THE MUSIC CONNECTION - - Vocabulary - Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Brass instruments; Musical instruments; Films for the hearing impaired